2022
DOI: 10.3389/feart.2022.962097
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the land use and land cover change in the period 2005–2020 in the province of Errachidia, the pre-sahara of Morocco

Abstract: The study investigates the land use and land cover (LULC) in Errachidia province (Pre-Saharan of Morocco) in the period 2005–2020. To this end, remote sensing (RS) tools such as LULC, the normalized difference vegetation index (NDVI), the normalized difference water index (NDWI), the Enhanced Vegetation Index (EVI), Gravity Recovery and Climate Experiment (GRACE) satellite data, and precipitations were processed and combined. The monitoring of LULC over this period reveals different changes in this area. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This declining trend of water was also reflected in the decrease in waterbodies in the entire studied area using MLC between 1991 and 2022. This negative trend was found also in a recent study on a provincial scale [61]. In contrast, this last method has demonstrated an increase in the urban area (built-up class), very remarkable in Errachidia city near the HED.…”
Section: Discussionsupporting
confidence: 68%
“…This declining trend of water was also reflected in the decrease in waterbodies in the entire studied area using MLC between 1991 and 2022. This negative trend was found also in a recent study on a provincial scale [61]. In contrast, this last method has demonstrated an increase in the urban area (built-up class), very remarkable in Errachidia city near the HED.…”
Section: Discussionsupporting
confidence: 68%
“…As for the urban area, the results of this study revealed an increase of 0.22 in this class of land, and a study by [102] showed an increasing trend in urban areas in the Errachidia province during the period of 2005-2020. This increase in urban land reflects the population growth and development of infrastructure in the region.…”
Section: Land Use and Land Cover Change In The Ziz Watershedsupporting
confidence: 48%
“…The stability of the open water category in the Ziz basin over time can be attributed to the natural characteristics of the water bodies, which are relatively resistant to changes in land use and climate. The water bodies in the study area are rare and the estimated change is slight since the area is arid, as mentioned by [102]. However, open water bodies in the region are also vulnerable to pollution, over-extraction, and other human activities that can lead to water quality degradation and the loss of biodiversity [110].…”
Section: Land Use and Land Cover Change In The Ziz Watershedmentioning
confidence: 99%
“…To extract relevant information on surface features such as vegetation, urban areas, soil or water, spectral indices (SI) are utilized, significantly enhancing the accuracy of LULC classification. [9]. The findings suggest that urban development has had an adverse impact on groundwater, soil quality and natural ecosystems.…”
Section: Introductionmentioning
confidence: 96%